Dampak Penggunaan Alat dan Mesin Pertanian terhadap Biaya Produksi Padi di Desa Pakatellu Kecamatan Kusan Hilir Kabupaten Tanah Bumbu - Ulfah, Maria (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Maria Ulfah (2018) This research, entitled " The Impact of AgriculturalMachinery And Means On The Cost Of Rice Production in Pakatellu Village, KusanHilir Subdistrict, Tanah Bumbu Regency." Under the guidance Dra. Hj. IkaChandriyanti, MP. This study wants to determine the impact of useful tools and agriculturalmachinery on rice production and rice production costs in Pakatellu Village. Theanalytical method used is a Paired sample t-test. The respondents were 75 farmers,determined by simple random sampling. Data processed using SPSS 23. The results indicate there is a change of rice yields before and after usingagricultural tools and machinery, and there is a reduction in the cost of the wage forplanting and harvesting labor because using tools and machinery. Therefore, theauthor suggests for farmers in Pakatellu and other villages that if there are still thosewho have not used agricultural implements and machinery to apply them.